European lobster Homarus gammarus aquaculture: Technical developments, opportunities and requirements. (22nd November 2021) - Hinchcliffe, James; Agnalt, Ann‐Lisbeth; Daniels, Carly L.; Drengstig, Asbj∅rn; Lund, Ivar; McMinn, Jane; Powell, Adam
Abstract: The European lobster ( Homarus gammarus ) has been the subject of aquaculture and related research efforts for the last 150 years, due to both the wild fishery and cultural value of the species. Since the middle of the 20th century, increasing anthropogenic pressure has led to a severe decline in wild fish and shellfish stocks, including H. gammarus, with some fisheries yet to recover. H. gammarus is amongst the most exclusive and valuable European shellfish products, and whilst management measures have been implemented to safeguard stocks, H. gammarus aquaculture is an increasingly credible approach to help to secure a sustainable lobster supply. Historically, this has been achieved by relatively small‐scale release of hatchery‐reared juveniles during stock enhancement programmes. Until recently, commercial attempts at farming have not been viable, mainly due to cost‐prohibitive technical challenges. At present, there are several promising approaches to overcome bottlenecks hampering commercialisation of lobster aquaculture. This review summarises new technical and husbandry innovations in H. gammarus culture since the start of the 21st century, including technological innovations, husbandry and expansion of the stock enhancement (release) and farming (production) sectors. Additionally, likely directions for both sectors in the coming decades are summarised, knowledge gaps identified and the societal support required to achieve further potential are discussed.